Randomized clinical trial: Direct‐acting antivirals as treatment for hepatitis C in people who inject drugs: Delivered in needle and syringe programs via directly observed therapy versus fortnightly collection. Issue 8 (26th May 2022) - Beer, Lewis; Inglis, Sarah; Malaguti, Amy; Byrne, Christopher; Sharkey, Christian; Robinson, Emma; Gillings, Kirsty; Radley, Andrew; Hapca, Adrian; Stephens, Brian; Dillon, John
Abstract: Hepatitis C virus (HCV) treatment in people who inject drugs (PWID) is delivered within settings frequented by PWID, such as needle and syringe programs (NSP). The optimal direct‐acting antiviral (DAA) dispensing regimen among NSP clients is unknown. This study compared cures (Sustained virologic response 12 weeks post‐treatment, [SVR12 ]) across three dispensing schedules to establish non‐inferiority of fortnightly dispensing versus directly observed therapy. The ADVANCE HCV study was a randomized, unblinded trial, recruiting PWID attending NSP in Tayside, Scotland, between January 2018 and November 2019. HCV‐positive participants were randomized to receive DAAs via directly observed therapy, fortnightly provision or fortnightly provision with psychological intervention. A modified intention to treat analysis was used to identify differences in cures between the three treatment regimes. The study was registered with clinicaltrials.gov ; NCT03236506. A total of 110 participants completed the study. 33 participants received directly observed therapy, with 90.91% SVR12 ; 37 received fortnightly provision, with 86.49% SVR12 and 40 received fortnightly provision and psychological intervention at treatment initiation, with 92.50% SVR12 . Analysis showed no significant difference in SVR12 ( p = 0.67). This study did not demonstrate a statistically significant difference in cure rate between groups. This provides evidence of the non‐inferiority of fortnightly dispensing of direct‐acting antivirals (DAAs) compared to directly observed therapy among PWID. It suggests that tight control of adherence through directly observed therapy dispensing of DAAs among this population offers no therapeutic advantage. Therefore, less restrictive dispensing patterns can be used, tailored to patient convenience.